Serum and CSF N-acetyl aspartate levels differ in multiple sclerosis and neuromyelitis optica. Issue 12 (27th May 2011) - Tortorella, C; Ruggieri, M; Di Monte, E; Ceci, E; Iaffaldano, P; Direnzo, V; Mastrapasqua, M; Frigeri, A; Amato, M P; Hakiki, B; Ghezzi, A; Lugaresi, A; et al.
Abstract : Background: The identification of biomarkers able to improve the differential diagnosis between multiple sclerosis (MS) and neuromyelitis optica (NMO) is challenging because of a different prognosis and response to treatment. Growing evidence indicates that brain and CSF N-acetyl aspartate (NAA) concentration is a useful marker for characterising different phases of axonal pathology in demyelinating diseases, and preliminary studies suggest that increased serum NAA levels may be a telltale sign of acute neuronal damage or defective NAA metabolism in oligodendrocytes. Objective: To evaluate whether serum and CSF NAA concentration differs in patients with MS and NMO. Design: Observational, multicentre, prospective, cross sectional study. Methods: Serum samples were collected from 48 relapsing–remitting MS, 32 NMO and 76 age matched healthy controls. Coeval CSF samples were available for all MS and for 8/32 NMO patients. NAA was measured in serum and CSF by liquid chromatography–mass spectrometry. Results: MS patients showed higher serum and CSF NAA levels than NMO patients, and higher serum NAA levels than healthy controls (p<0.001). High serum NAA values, exceeding the 95th percentile of serum NAA values in healthy controls, were found in 100% of patients with MS and in no patient with NMO. No differences in serum NAA levels were found between NMO and healthy controls. In MS, serum and CSF NAA levels correlated with disability score. Conclusions: Determination of serum and CSF NAA levels may represent a suitable tool in the diagnostic laboratory workup to differentiate MS and NMO.